Exploration of zwitterionic cellulose acetate antifouling ultrafiltration membrane for bovine serum albumin (BSA) separation. (1st June 2017) - Liu, Yang; Huang, Haitao; Huo, Pengfei; Gu, Jiyou
Highlights: Zwitterionic cellulose acetate (ZCA) was successfully prepared by oxidization, Schiff base and quaternary amination reaction. ZCA membrane exhibited enhanced hydrophilicity and water permeability. ZCA membrane showed improved antifouling property and long-term residence stability. ZCA membrane seems promising for potential applications in protein separation. Abstract: This study focused on the preparation of a new kind of membrane material, zwitterionic cellulose acetate (ZCA), via a three-step procedure consist of oxidization, Schiff base and quaternary amination reaction, and the fabrication of antifouling ZCA ultrafiltration membrane by the non-solvent-induced phase separation method (NIPS). The morphologies, surface chemical structures and compositions of the obtained CA and ZCA membranes were thoroughly characterized by field emission scanning electron microscopy (FE-SEM) with energy dispersive X-ray (EDX) spectroscopy, Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS), respectively. Meanwhile, the thermal stability, porosity and average pore size of two investigated membranes were also studied. As a result, the ZCA membrane displayed significantly improved hydrophilicity and water permeability compared with those of the reference CA membrane, despite a slight decrease in the protein rejection ratio. According to the cycle ultrafiltration performance of bovine serum albumin (BSA) solution and protein adsorption experiment, ZCA membrane exhibited better flux recovery property and fouling resistant ability, especially irreversible fouling resistant ability, suggesting superior antifouling performance. This new approach gives polymer-based membrane a long time life and excellent ultrafiltration performance, and seems promising for potential applications in the protein separation.